Dermoid Cyst of the Pancreas: A Report of an Unusual Case and a Review of the Literature - Aynur Albayrak; Umran Yildirim; Metin Aydin (Case Reports in Pathology)
Pancreatic dermoid cysts are a rare entity. Preoperative diagnosis is difficult. The diagnosis is generally taking intraoperative. A 20-year-old female presented with epigastric pain without nausea, vomiting, diarrhea, fever, jaundice, and weight loss of one-month duration. Ultrasonography and computed tomography showed a smooth borders, solid, hyperechoic tumor within midline abdomen, without any connection to the stomach or spleen. At surgery, the entire mass was excised off of the head and inferior part of pancreas. Histopathologic evaluation revealed the rare diagnosis of a dermoid cyst. The diagnosis is difficult preoperatively in evaluating cystic pancreatic lesions by imaging. Therefore, we want to summarize the literature on this rare entity knowledge.